The Psychosocial Impact of Chronic Facial Dermatoses in Adults - Ozcan, Yunus; Sungur, Mehmet Ali; Yaman Özcan, Begüm; Eyüp, Yavuz; Özlü, Emin (Dermatology Practical & Conceptual, 2023)
Introduction: Skin diseases have negative psychological and social consequences, especially when they are chronic and affect a visible area of the body, such as the face.Objectives: The purpose of this study is to investigate and compare the psychosocial impact of three common chronic dermatoses of the face: acne, rosacea, and seborrheic dermatitis.Methods: The Dermatology Life Quality Index (DLQI), Hospital Anxiety and Depression Scale (HADS), and Social Appearance Anxiety Scale (SAAS) were used to compare acne, rosacea, and seborrheic dermatitis patients and healthy controls. The relationships between DLQI, HADS, and SAAS results were investigated, as well as their associations with disease duration and severity.Results: The study included 164 acne patients, 134 rosacea patients, 120 seborrheic dermatitis patients, and 124 controls. The patient groups had significantly higher DLQI, HADS, and SAAS scores than the control group. Rosacea patients had the highest DLQI and SAAS scores, as well as the highest anxiety prevalence. Patients with seborrheic dermatitis had the highest rate of depression. The DLQI, HADS, and SAAS results were moderately correlated with each other, but their relationship with disease duration and severity was insignificant or weak at best.Conclusions: Chronic facial dermatoses have a detrimental impact on mood and quality of life. Although patients with acne, rosacea, and seborrheic dermatitis have distinct lesions, the outcomes in terms of quality of life, anxiety, and depression are largely similar. Furthermore, these patients have a higher prevalence of social anxiety as a result of their overall appearance rather than just their faces.